Awareness, Knowledge, and Misperceptions Related to Nonalcoholic Fatty Liver Disease in a Community Sample of Mexican-Origin Women: A Mixed Methods Study - Morrill, Kristin E.; Crocker, Rebecca M.; Hingle, Melanie D.; Thomson, Cynthia A.; Garcia, David O. (Frontiers in Public Health, 2021)
Introduction: Mexican-origin women suffer disproportionate rates of nonalcoholic fatty liver disease (NAFLD) and research on how to tailor NAFLD treatment interventions for this population is lacking. Objectives: The purpose of this study was to assess awareness, knowledge, perceptions, and information sources related to NAFLD in a community-based sample of Mexican-origin women. Methods: This study employed a convergent parallel mixed-methods approach and consisted of a brief questionnaire (n=194) and interviews (n=26) among Mexican-origin women recruited from community-based settings including health fairs, churches, and community events. Participants were eligible if they identified as Mexican-origin, had a BMI > 25 kg/m2, were 18-64 years of age, had the ability to speak, read, and write in English and/or Spanish, and provided informed consent. A purposeful sampling approach was used to recruit a subset of women (n=26) with confirmed liver steatosis indicative of NAFLD (controlled attenuation parameter >280 dB/m) who completed the questionnaire. The twenty-six participants then completed one on one, in-depth semi-structured interviews to ascertain their knowledge and understanding of NAFLD. Results: Qualitative findings revealed low awareness of risk factors for liver disease, NAFLD specifically. Knowledge of liver disease tended to center around cirrhosis, a condition many participants reported was prevalent in their families. Quantitative and qualitative findings both found information sources for NAFLD and liver disease to be predominantly friends, family, and media. Interviews revealed a misperception related to NAFLD risk that liver disease was only caused by high alcohol intake. Conclusion: Low levels of NAFLD awareness and knowledge warrant the need for greater efforts to educate the general population, perhaps by integrating NAFLD education into existing type 2 diabetes educational campaigns and prevention interventions. Additionally, further elicitation research conducted in Mexican-origin adults is needed to elucidate key factors within behavioral-theory constructs that can be targeted in future interventions tailored to this unique population.